PENGARUH PERSEPSI PENERAPAN PASAL 6 AYAT 1 HURUF a UU NO. 5 TAHUN 2011 TENTANG AKUNTAN PUBLIK (SYARAT PENDIDIKAN) TERHADAP MOTIVASI, OPTIMISME DAN PERENCANAAN KARIR MAHASISWA JURUSAN AKUNTANSI - Ertanto, Veven; Hasan, Amir; Sofyan, Azhari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aimed to axamine the effect of the perception of article 6 paragraph 1 letter of a Act No.5 of 2011 about public accounting (education requirements) on motivation, optimism and career planning accounting majors to be professional public accountan in the future. This research took a Population from accountancy student, Economic Faculty from Riau University, State Islamic University of Sultan Syarif Kasim, and Lancang Kuning University 2009-2012. Meanwhile the sample in this study were accounting students with criteria that was still active as a students, has received a course of audit concentration and heard of a Public Accounting Act No.5 of 2011, so that the number of accounting students who fit these criteria above totals 300 respondents. Samples based on the quota method sampling. Data of this research is then processed using simple regression linear method, over statistics Application SPSS 17. The results of this study indicated that the application of article 6 paragraph 1 letter of a Act No.5 of 2011 about public accounting (education requirements) significantly effect the motivation and career planning student accounting. Whereas application of article 6 paragraph 1 letter of a Public Accounting Act No.5 of 2011 no effect significantly to optimism student accounting. These results explain that the regulation of public accountants effect on student motivation by 71,2%, optimism by 19,2% and career planning by 67,4% while the rest is influenced by other factors.Keywords: Motivation, Optimism, Career Planning, Public Accounting Act